Fractional parts of powers of real algebraic numbers - Bugeaud, Yann (Comptes Rendus. Mathématique, 2022)
Let $α $ be a real algebraic number greater than $1$. We establish an effective lower bound for the distance between an integral power of $α $ and its nearest integer.